(untitled) (Acta Scientiarum. Biological Sciences, 2017)
A taxonomic study of species of the genus Gomphonema Ehrenberg (Bacillariophyceae) was performed in alotic environment (Ipoitã Channel) of the Upper Paraná River Floodplain. Samplings were performed in June, September and December 2013 and February 2014. Two petioles of Eichhornia azurea (Sw) Kunth were sampled at three different sites in the channel. Twelve species and two taxonomic varieties were identified. All species identified were recorded at the sampling site 3, loca ated close to the Ivinhema River. The lowest number of taxa occurred at the sampling site 1 (9 specific and infra specific taxa), in the confluence with the Paraná River. All taxa of Gomphonema were the first record for the Upper Paraná River Floodplain. Our results emphasize the lack of taxonomic studies for the region and the importance thereof to the knowledge of biodiversity.